Serological Protection 5–6 Years Post Vaccination Against Yellow Fever in African Infants Vaccinated in Routine Programmes - Idoko, Olubukola T.; Domingo, Cristina; Tapia, Milagritos D.; Sow, Samba O.; Geldmacher, Christof; Saathoff, Elmar; Kampmann, Beate (Frontiers in Immunology, 2020)
Introduction Although effective live attenuated yellow fever (YF) vaccines have been available for over 9 decades sporadic outbreaks continue to occur in endemic regions. These may be linked to several factors including epidemiological factors such as vector and intermediate host distribution or vaccine coverage and efficacy. The World Health Organization’s research priorities include gathering systematic evidence around the potential need for booster vaccination with YF vaccine whether this follows full or fractional doses in children. Knowledge on the longevity of response to YF vaccine and the implications of this response needs to be consolidated to guide future vaccination policy. Methods We measured anti-YF IgG by microneutralization assay in a group of 481 African infants who had received YF vaccine as part of routine EPI programmes, to explore serological protection from YF 5 to 6 years post YF vaccination, as well as the effect of co variates. Findings Notably, 22.2% of the cohort had undetectable antibody concentrations, with another 7.5% revealing concentrations below the threshold of seropositivity of 0.5 IU/mL. Sex, season, country and time since vaccination did not affect the longevity of antibody concentration or having antibody concentrations above a defined threshold. Conclusion Roughly 30% of children in this cohort did not demonstrate anti-yellow fever antibody concentrations above the defined threshold of protection, with 20% having no demonstrable antibody. Knowledge on the longevity of response to YF vaccine and the implications needs to be consolidated to guide future vaccination policy.